Analisis Penggunaan Bahan Bakar Solar dan Pertamina Dex Terhadap Emisi Gas Buang Mesin Diesel - Muhammad Iskandar Musa; Haruna Haruna (Seminar Nasional LP2M UNM, 2019)
This research is an experimental study which aims to determine the level of exhaust emissions (smoke) produced by diesel fuel and Pertamina Dex. The smoke opacity meter is used to retrieve data about the thickness of the exhaust gases of the two types of fuel, namely diesel fuel and Pertamina Dex on diesel engines. Experimental test results show a comparison of diesel engine exhaust emissions using diesel fuel and Pertamina Dex fuel. RPM 500 Solar by 1.5% and Dex pertamina by 2.3% experienced smoke increase of 0.8%, RPM 1000 Solar by 5.9% and pertamina Dex 8.9% experienced smoke increase of 0.3%, RPM 1500 Solar by 30.9% and Pertamina Dex 25.6% decreased smoke by 5.3%, RPM 2000 Solar by 52.1% and Pertamina Dex 43.9% decreased smoke by 8.2%, and RPM 2500 Solar by 74, 4% and Pertamina Dex 65.8% decreased 8.6%.